Pollution, climate extremes, and psychosocial stress: emerging environmental risks for cardiovascular disease: a review - Aher, Aman; Doad, Jagroop; Fappi, Alan; Wasir, Amanpreet S.; Agarwal, Aditi; Shah, Netra (International Journal Of Community Medicine And Public Health, 2025)
Environmental stressors like pollution, extreme temperatures, and psychosocial stress are increasingly recognized as significant but underappreciated contributors to cardiovascular disease (CVD), including cardiomyopathy. These exposures disrupt cardiovascular homeostasis through oxidative, inflammatory, and metabolic pathways, yet their integrated mechanisms remain poorly addressed in clinical risk frameworks. We aim to bridge this gap. We searched PubMed, Embase and Scopus for studies linking pollution, extreme climate changes and psychosocial stress with cardiomyopathy or other CVD outcomes using preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. A total of 17 epidemiologic and experimental studies reporting CVD outcomes and mechanistic data were included. Air pollution (PM2.5 and PM10) was significantly associated with increased systolic and diastolic blood pressure with 0.2-0.6% higher all-cause mortality, and 0.3-0.7% cardiovascular mortality. These outcomes were mediated by reactive oxygen species (ROS) generation, endothelial dysfunction, and systemic inflammation. Noise and light pollution disrupted circadian rhythms, elevating cortisol, IL-6, and TNF-α levels. Heat exposure triggered autonomic imbalance and endothelial injury via heat shock protein activation, increasing arrhythmia risk. Shared molecular mechanisms included eNOS uncoupling, NADPH oxidase–mediated ROS production, and Ly6C⁺ monocyte activation, promoting atherogenesis and plaque instability. Environmental stressors are emerging, modifiable, and underrecognized contributors to cardiovascular morbidity and mortality. Despite varied triggers, these exposures converge on common mechanistic pathways that fuel myocardial dysfunction. Our findings underscore a need for preventive action. Targeted preventive strategies including air quality regulation, heat stress mitigation, urban greening, and psychosocial support programs are urgently needed. Future research should further delineate these pathways and guide the integration of environmental risk into cardiovascular disease prevention and policy.